Identifying Deliberation in Social Movement Assemblies: Challenges of Comparative Participant Observation - Christoph Haug; Simon Teune (Journal of Deliberative Democracy, 2008)
Contemporary social movements can serve as a critical case for the empirical study of deliberation. In countless face-to-face meetings activists often discuss long hours before a decision is reached. In this context, we try to analyse the conditions under which deliberation is successfully employed as a method of discursive conflict resolution. As we develop participant observation in a comparative approach we encounter three methodological challenges which this paper addresses. First, we look at some characteristics of the global justice movements, briefly addressing the different settings in which controversial discussions occur. Second, we give a rationale for applying a semi-standardised multi-level participant observation in order to allow the collection of comparable data by various researchers in several countries. Focusing on participant observation on the level of controversial discussions we thirdly conceptualise competitiveness, power, and asymmetry as three theoretical dimensions to identify eight different practices of discourse, one of them being deliberation. We are currently implementing this model for regular observations of group meetings on a local, national and European level. First results should be available in the near future.